On farming systems survey for study of on-farm conservation of apple landraces in Karvak village in Khazarasp District of Khorezm Province of Uzbekistan - Turdieva, Muhabbat; Amri, Ahmed; Imtiaz, Muhammad; Bishaw, Zewdie (2025)
On farming systems survey for study of on-farm conservation of apple landraces in Karvak village in Khazarasp District of Khorezm Province of Uzbekistan.